Perkawinan Beda Agama Perspektif Majelis Ulama Indonesia dan Muhammadiyah - Mifatakhul Bil Ibad (State Islamic University (UIN) of Sunan Ampel, 2019)
This article discusses interfaith marriage law according to the fatwa of the Indonesian Ulema Council and Muhammadiyah. According to the MUI’s fatwa, interfaith marriages are unlawful with the proposition of chapter of al-Baqarah verse 221. While Muhammadiyah believes interfaith marriages are permissible on the basis of al-Maidah verse 5. MUI forbids interfaith marriages because it can lead to conflicts between Muslims and cause unrest in the community. Muhammadiyah allows interfaith marriages because in Islamic history it is known that the Prophet Muhammad was married to a Christian woman from Egypt, namely Maria al-Qibthiyyah. Some of the Companions of the Prophet also married the women of the Book. MUI equates ahlu al-Kitab (Nashrani and Jewish) including the category of polytheists, while Muhammadiyah considers that women from ahlu al-Kitab does not include polytheists as stated in chapter al-Baqarah verse 221. This is because according to Muhammadiyah there are many verses that distinguish between ahlu al-Kitab and polytheism by considering the linguistic analysis in chapter al-Baqarah verse 105 and al-Bayyinah verse 1.